The Mainstreaming Policy of Religious Moderation Education in West Sulawesi Province - Mukhlis Latif; Fatah Syukur; Uswatunnisa Uswatunnisa; Zulhilmi Paidi (Universitas Islam Negeri Walisongo Semarang, Indonesia, 2023)
This research is oriented to describe and elaborate on the mainstreaming policy of religious moderation on education in West Sulawesi Province, which the government is currently reviewing through the Ministry of Religion Affairs. The study conducted qualitative methods with specific data collection. It analyzed the instruments and found that the informants, consisting of educators and religious figures, deeply understood religious moderation based on the al-Qur'an and hadith, which emphasized Islam as a moderate religion. The principle of restraint (Wasathiyyah) in Islam is, in fact, equivalent to the direction or value of religious moderation programmed by the current government. Then, religious moderation is to be implemented in education. In that case, some components should be prepared carefully to avoid overlapping or duplicating with other programs. For example, several implementation models, with their respective advantages and disadvantages, include autonomous, integrative, collaborative, and enrichment models in education. In addition, what is also very urgent to formulate is the right curriculum, tools and learning designs, and competencies of educators, including an assessment tool which, of course, is more oriented towards attitudes and behavior no longer trapped in the pathology of learning that has been ongoing, more focused on fulfilling the cognitive domain.